Netupitant / palonosetron with dexamethasone for preventing nausea and vomiting in patients with multiple myeloma receiving high-dose melphalan for autologous hematopoietic stem cell transplantation: a single-center experience - N. E Mochkin; N. S. Shorokhov; V. O. Sarzhevskiy; V. S. Bogatyrev; A. A. Samoylova; A. A. Rukavitsyn; E. G. Smirnova; A. E. Bannikova; A. A. Mamedova; Yu. V. Protopopova; V. Ya. Melnichenko (Онкогематология)
Aim. To assess efficacy of netupitant / palonosetron with dexamethasone for chemotherapy‑induced nausea and vomiting in 20 patients with multiple myeloma who underwent autologous hematopoietic stem cell transplantation.   Materials and methods. The inclusion criteria were patients aged ≥18 years with a diagnosis of multiple myeloma, eligible for transplantation and a favorable response (according to the International Myeloma working Group criteria after induction therapy). Netupitant / palonosetron was administered at a dose of 1 capsule (300 mg netupitant; 0.5 mg palonosetron) 1 h before the start of chemotherapy conditioning (day –3) and dexamethasone was administered at day – 3 (12 mg), day – 2…0 (8 mg). Intravenous metoclopramide 10 mg was used as a rescue antiemetic when needed. Patients were evaluated every day for up to 12 days after autologous hematopoietic stem cell transplantation. The primary endpoint was the rate of complete response (no emesis and no rescue medication during 120 h after conditioning). Secondary endpoints were defined as the rate of complete response during the acute phase (0–24 h) and delayed phase (25–120 h) from the start of high‑dose melphalan. The safety of combination was also evaluated. 20 patients were included. The median age was 53.5 (37–67) years.   Results. Netupitant / palonosetron with dexamethasone prophylaxis showed a high efficacy in preventing chemotherapy‑induced nausea and vomiting during the high‑dose melphalan conditioning period. The primary outcome was largely achieved with a complete response observed in 14 (70 %) patients at 120 h. The complete response rate during the acute phase was 70 % (n = 14). during the delayed phase, the complete response rate was 95 % (n = 19). Grade 1 nausea and vomiting were experienced by 70 % of the patients, grade 2 – by 30 % of patients. No patients had grade 3–4 nausea or vomiting. Intravenous metoclopramide 10 mg was used in 30 % (6 patients).   Conclusion. Firstly in Russia we assess efficacy of netupitant / palonosetron with dexamethasone for chemotherapy‑induced nausea and vomiting in 20 patients with multiple myeloma who received high‑dose melphalan for autologous hematopoietic stem cell transplantation.